Effect of Ionic Liquid Electrolyte on Electrochemical and Electrocatalytical Behaviours of Tri-Iron Cluster - LI*, ZHIMEI; ZENG, XIANGHUA; ZHONG, DINGYI; HE, FANG; NIU, ZHIGANG (Asian Journal of Chemistry, 2009)
The tri-iron cluster, [Fe3(μ3-S)2(CO)9], has been reported as acatalysis to proton reduction at low overpotential. In this paper, theelectrochemical behaviour of the tri-iron cluster and its catalytic effecton hydrogen evolution were investigated further by using ionic liquid(1-dodecane-3-methylimidazolium tetrafluoroborate, IL) as electrolytein dichloromethane, considering that IL has unique chemical and physicalproperties. In contrast to the conventional electrolytes (such as [NBu4]BF4),the IL electrolyte increases the stability of the monoanionic radical generatedfrom the first reduction and the electrocatalytic efficiency on protonreduction has also been improved.